2008 Eighth IEEE International Conference on Advanced Learning Technologies 2008
DOI: 10.1109/icalt.2008.212
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Student Model on Learning

Abstract: Our goal in this study was to compare the effectiveness of displaying the open student model as a set of skillometers versus concept maps. The data suggests that concept maps are significantly more effective than a set of skillometers when answering questions that require synthesizing an overview of the topic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The inspectable s tudent model is a holistic presentation of the system’s assessment of student skill across the entire domain. The use of inspectable student models, such as skill-o-meters10,44,45, has been well-established as a cognitive scaffold. But there is no conclusive data related to its use as a metacognitive scaffold.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inspectable s tudent model is a holistic presentation of the system’s assessment of student skill across the entire domain. The use of inspectable student models, such as skill-o-meters10,44,45, has been well-established as a cognitive scaffold. But there is no conclusive data related to its use as a metacognitive scaffold.…”
Section: Discussionmentioning
confidence: 99%
“…This makes it possible to individualize instruction without necessarily anticipating specific interactions. Despite the enormous potential for medical education, there have been few ITS developed in Medicine 5–10, only a small number of which have been evaluated 1113.…”
Section: Introductionmentioning
confidence: 99%
“…ITSs support “leaning-by-doing,” and provide individualized support, point out errors, and organize content to cater to the needs of the individual when the teacher has limited time to spend (Corbett, Koedinger, & Hadley, 2002; Koedinger & Aleven, 2007; VanLehn, 2006, 2011). Although there is a great potential for the use of medical ITS, few of these systems have been fully developed (e.g., Azevedo & Lajoie, 1998; Clancey, 1987; Crowley & Medvedeva, 2006; Lajoie & Azevedo, 2006; Lajoie, 2009; Maries & Kumar, 2008; Obradovich et al, 2000; Rogers, 1995; Sharples et al, 2000; Smith et al, 1998), a smaller number of which have been empirically evaluated (Crowley et al, 2007; El Saadawi et al, 2008; Woo et al, 2006). …”
Section: Introductionmentioning
confidence: 99%
“…To illustrate, Figure 1 gives excerpts from: a simple skillometer-type visualization (from ; similar simple bullets visualization (from Brusilovsky & Yudelson, 2008); treemap (from Brusilovsky et al, 2013); and two structured views showing concept nodes and links in a concept map (from ; and a hierarchical network visualization (from Bull, Johnson, Masci, & Biel, 2016). While some studies have found that simple indicators like skillometers are preferred by students (Duan, Mitrovic, & Churcher, 2010), other studies support more complex representations such as concept maps (Maries & Kumar, 2008), for example, as tools to represent and refine assessment claims on learners knowledge (Zapata-Rivera et al, 2007). Given the di↵erences between relative benefits and limitations of the various visualizations, consideration needs to be given as to whether simple or complex visualizations are more suitable for a specific case.…”
Section: Related Workmentioning
confidence: 99%